Fatigue Factors, Management, and Flight Training Safety Among Cadet Pilots at the Indonesian Aviation Academy Banyuwangi - Agung Wahyu Wicaksono; Deodatus Januarius Odi Wayam; Safitri Era Globalisasi (Jurnal Penelitian, 2026)
Fatigue is a critical human-factors hazard in flight training because it can impair attention, procedural memory, communication, and aircraft control. This study examined the dominant causes of fatigue among cadet pilots at the Indonesian Aviation Academy Banyuwangi, the strategies used to manage it, and the institutional implications for flight training safety. A descriptive qualitative case-study design was supported by an exploratory questionnaire, direct observation of training schedules, semi-structured interviews, and a literature review. Thirty-one cadets in the CPL-IR phase with more than 50 flight hours completed a seven-item questionnaire, and four cadets representing the participating cohorts completed interviews guided by 15 questions. Questionnaire data were summarized using frequencies, while interview and observation data were analyzed through data condensation, thematic display, and conclusion verification. Twenty-nine of 31 cadets reported experiencing fatigue. The most frequently reported contributors were insufficient sleep (13 responses), high physical workload (10), and insufficient nutrition (8). Concentration and procedural disruption were the most common consequences (18 responses). Interviews further showed that compressed schedules, consecutive flight, simulator, academic, hangar, and dormitory duties created cumulative fatigue, while institutional responses to fatigue reporting were inconsistent. The study is novel in framing cadet fatigue as an interaction between individual recovery practices and institutional scheduling conditions. It recommends an academy-level Fatigue Risk Management System incorporating non-punitive reporting, schedule-risk assessment, pre-flight fitness checks, protected rest, and nutrition and hydration support.